Die breuk tussen die Christendom en die Jodedom in die eerste twee eeue nC - H. F. Stander (Verbum et Ecclesia, 1989)
The break between Christianity and Judaism in the first two centuries AD It is argued that a radical break between Christianity and Judaism originated in the second half of the first century AD. This sharp separation persisted in the subsequent centuries. In this article the relationship between the early Christians and the Jews in the first two centuries is studied. The issue is approached from three different angles, namely (a) How did the pagans (the Greeks and the Romans) see the Christians? (b) How did the Jews behave towards the Christians? (c) How did the Christians behave towards the Jews? All statements are based on quotations from primary texts outside the New Testament.